2022
DOI: 10.3389/feduc.2022.1014693
|View full text |Cite
|
Sign up to set email alerts
|

Assessing academic impairment in college students with disabilities: A new measure to promote evidence-based accommodation granting

Abstract: College students with disabilities may be entitled to academic accommodations such as additional time on exams, testing in a separate setting, or assistance with note-taking. To receive accommodations, students must request services from their college and show that they experience substantial limitations in academic functioning. Without norm-referenced data, it is difficult for college disability support professionals to determine if students’ self-reported academic problems reflect substantial limitations cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Symptomatology of attention-deficit/hyperactivity disorder is defined as the presence of symptoms of inattention and/or hyperactivity and impulsivity (American Psychiatric Association, 2013). While the symptoms of hyperactivity and impulsivity are highly prevalent in children with diagnosed ADHD, in adolescents and young adults we observe problems with attention, organization, executive functioning, time management, study skills, anxiety and mood (Weis et al, 2019). All these symptoms could be a barrier to successful functioning and performing in higher education.…”
Section: Attention Deficit Disorders (Adhd)mentioning
confidence: 82%
See 1 more Smart Citation
“…Symptomatology of attention-deficit/hyperactivity disorder is defined as the presence of symptoms of inattention and/or hyperactivity and impulsivity (American Psychiatric Association, 2013). While the symptoms of hyperactivity and impulsivity are highly prevalent in children with diagnosed ADHD, in adolescents and young adults we observe problems with attention, organization, executive functioning, time management, study skills, anxiety and mood (Weis et al, 2019). All these symptoms could be a barrier to successful functioning and performing in higher education.…”
Section: Attention Deficit Disorders (Adhd)mentioning
confidence: 82%
“…All these symptoms could be a barrier to successful functioning and performing in higher education. Weis et al (2019) explored the way how clinicians report about college students with ADHD. Based on the results, they focus mostly on symptoms rather than barriers and accommodations, in their sample, 32% of clinicians described barriers and only 42% described some history of accommodations.…”
Section: Attention Deficit Disorders (Adhd)mentioning
confidence: 99%
“…Nevertheless, it was also found that students predominantly employ recorded lectures as supplementary to enhance the lectures. They can cater to students’ different needs, learning preferences, and difficulties, including Attention-Deficit/Hyperactivity Disorder (ADHD) (Weis et al, 2019; Witthaus & Robinson, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Students with ADHD in higher education require instructional accommodations (Newton et al, 2014). Therefore, there is a need to leverage technology so that various formats are available, such as online handouts, tutorials, and recorded lectures (Weis et al, 2019). However, although academic accommodations are frequently provided to students with ADHD (such as testing to be administered in a separate room to reduce distractions), surprisingly, little research demonstrates the effectiveness of recorded lectures for these students.…”
Section: Introductionmentioning
confidence: 99%